Co-digestion of wastewater sludge with food waste and green cuttings - optimization of methane production - Kolbl Repinc, Sabina (Acta hydrotechnica, 2022)
This article outlines our investigation into the methane production of wastewater sludge (WWS) from a wastewater treatment plant (WWTP) and a mixture of WWS with food waste (FW) and green cutting (GC). To determine the optimal mixture, two methane potential experiments were performed using the Automatic Methane Potential Test System (AMPTS II). In the first experiment, WWS and FW were used. The highest methane potential was measured in FW, and the lowest in WWS. The combination of both substrates did not approach the methane potential of FW (241.5 ± 15.7 mL CH4/g VS). In second experiment, we combined WWS and GC. The highest methane potential was obtained at 5.1% addition of GC to the WWS (relative to the organic load). This methane potential was 7.5% higher than the methane potential of WWS, which was 470 ± 17 mL CH4/g VS. We calculated the optimal mixture of both experiments using the simplex lattice design method. In experiment one, the model had relatively good fit to the measured values, however in the second experiment the differences were significant
Keywords: anaerobic digestion; anaerobna presnova; blato; food waste; green cutting; metanski potencial; methane potential; odpadna hrana; wastewater sludge; zeleni odrez